Analysis of Indonesian Startup Companies Affected By the Bubble Burst (Case Study on PT GoTo Gojek Tokopedia Tbk.) - Jumiati, Jumiati; Atman Maulana, Hutomo (Politeknik Negeri Bengkalis, 2024)
The phenomenon of mass layoffs and falling stock prices of Indonesian startups when they have just conducted an Initial Public Offering (IPO) at a time of increasing startup growth during the pandemic, assumes the occurrence of a bubble burst phenomenon in Indonesian startups. This study tries to investigate the phases of the emergence of a speculation bubble in the startup PT GoTo Gojek Tokopedia Tbk by using the Kindleberger-Minsky model on GoTo. This research is qualitative research and uses library research methods by collecting data from various written sources such as books, articles, journals and existing research. The results of this study indicate that GoTo does not meet the bubble burst criteria based on the theory of bubble burst emergence patterns by Kindleberger-Minsky and there are no typical signs of speculation bubbles as seen in historical bubbles. .Keywords: Startup, Bubble Burst, Speculative Bubble Phases